2003
DOI: 10.1002/ijc.11277
|View full text |Cite
|
Sign up to set email alerts
|

Energy restriction and the risk of spontaneous mammary tumors in mice: A meta‐analysis

Abstract: Our meta-analysis was aimed at providing a systematic review of the literature regarding the effect of energy restriction on spontaneous mammary tumors in mice and at providing a more precise pooled (summary) estimate of the risk of mammary tumors. A sensitivity analysis was conducted to obtain insight in potential heterogeneity between the animal studies. A literature search was conducted with the following terms to identify relevant articles: animal studies, mammary tumors, fat restricted, dietary carbohydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 31 publications
3
97
1
1
Order By: Relevance
“…Prior to the current study, widely documented as the greatest environmental modulator of mammary tumor development in rodents (26). By comparison, unlimited access to high metabolizable energy food increased tumor incidence by only 90%, produced a modest 1.33 relative risk for malignancy, and had no effect on tumor growth (27).…”
Section: Discussionmentioning
confidence: 76%
“…Prior to the current study, widely documented as the greatest environmental modulator of mammary tumor development in rodents (26). By comparison, unlimited access to high metabolizable energy food increased tumor incidence by only 90%, produced a modest 1.33 relative risk for malignancy, and had no effect on tumor growth (27).…”
Section: Discussionmentioning
confidence: 76%
“…The NXS2 neuroblastoma line in mice induces consistent and reproducible metastases in a pattern that resembles the clinical scenario observed in neuroblastoma patients at advanced stages of the disease (31). Experimental metastases in the liver, kidneys, adrenal gland, and ovaries were observed after 25-30 days of the inoculation with 200,000 NXS2 cells (Table S1) as described in ref.…”
Section: Short-term Starvation Prevents the Death Of Mice But Not Of mentioning
confidence: 75%
“…Experimental metastases in the liver, kidneys, adrenal gland, and ovaries were observed after 25-30 days of the inoculation with 200,000 NXS2 cells (Table S1) as described in ref. 31. The tumor development and survival of the NXS2/STS/Eto group was significantly different from that of the NXS2 group (P Ͻ 0.001; Fig.…”
Section: Short-term Starvation Prevents the Death Of Mice But Not Of mentioning
confidence: 87%
See 1 more Smart Citation
“…Along with this life span extension is a reduction in chronic diseases that are common to mankind, reviewed in Hursting et al [6]. A recent meta-analysis of 14 experimental studies found that energy restriction resulted in a 55% reduction in spontaneous tumors in laboratory mice [7]. Calorie restriction inhibited induced mammary tumors in mice [8] and suppressed implanted tumor growth and prolonged survival in energy restricted mice [9].…”
Section: Reviewmentioning
confidence: 99%